Transforming Tofu Wastewater into Sustainable Organic Fertilizer: A Fermentation Approach with EM4 and Coconut Water - Pungut; Putri, Hrismalia Octavianindhita; Al Kholif, Muhammad; Fitria, Firda Lutfiatul (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
This growing need for sustainable agriculture has made using recycled waste material in plant cultivation a significant area of research. The tofu industry, as a leading producer of nitrogen (N), phosphorus (P), and potassium (K)-rich wastewater, is a valuable substrate resource for microbial fermentation. The application of solid-state fermentation using EM4 with coconut water under aerobic and anaerobic processes works towards acidification of DM, increasing bioavailable nutrients and minimizing environmental implications from untreated wastewater discharge. This study determined the feasibility of fermenting tofu wastewater with coconut water and EM4 to produce liquid organic fertilizer and analyzed the product’s N, P2O5, K2O, C-organic, and C/N ratio. Fermentation occurred at 4:1 of tofu wastewater: fermentation materials, with EM4 concentrations of 10%, 25%, and 50% under anaerobic conditions for 14 days. The fertilizer produced was analyzed and compared with liquid organic health fertilizer according to nonstandard percent by Minister of Agriculture no. 70/Permentan/SR.140/10/2011. Results showed that fermentation increased tofu wastewater’s protein and amino acid contents. The highest nitrogen content (3.09 ± 0.023%) was obtained by treatment C (50% EM4), meeting standard requirements (3-6% N). The K2Oconcentration of treatment C peaked at 3.28 ± 0.025% (K2O) within the acceptable range (3-6% K2O). The C-organic content in treatment C reached 10.5 ± 0.094%, exceeding the minimum quality (6%). The P2O5 contents never exceeded the maximum limit (2.22 ± 0.0057%). Although it indicates a rapid-acting fertilizer, the C/N ratio remained low for all treatments.